VEGF and VEGF type C play an important role in angiogenesis and lymphangiogenesis in human malignant mesothelioma tumours - Ohta, Y (Nature Publishing Group, 1999)
The vascular endothelial growth factor (VEGF) family is a novel regulator of endothelial cell proliferation. We assessed the mRNA expression of VEGF, VEGF type C (VEGF-C) and their receptors together with the microvessel density (VD) and microlymphatic vessel density (LVD) in pursuit of their connection and prognostic value in malignant pleural mesothelioma (MPM). We used four human MPM cell lines, 54 MPM tumours and five normal pleural tissues. Expression levels for receptors and ligands were assessed by semiquantitative reverse transcriptase polymerase chain reaction analysis. Microvessels were highlighted by immunohistochemical staining for factor VIII. The discrimination of lymphatics was performed by enzyme-histochemistry for 5′-nucleotidase after adequate inhibition of non-specific activity. The expression levels of VEGF, VEGF-C and VEGFRs were high in all MPM cell lines. The percentages of tumours with higher expression compared to the mean values of normal pleural tissues were 31.5% (17/54) for VEGF, 66.7% (36/54) for VEGF-C, 20.4% (11/54) for fms-like tyrosine kinase (flt)-1, 42.6% (23/54) for kinase insert domain-containing recepter (KDR) and 59.3% (32/54) for flt-4. Significant positive correlations were found between VEGF-C and flt-4, VEGF and KDR, VEGF and flt-1 in tumour tissues. The association between LVD and VEGF-C expression level was especially strong (P < 0.0001, r = 0.63). There were also significant correlations between LVD and flt-4, and VD and VEGF. No correlation, however, was found between LVD and nodal metastasis. VD was a negative prognostic indicator in this study. The associations between VEGF/VEGF-C and vessel density suggest that these factors play an important role in angiogenesis and lymphangiogenesis in this tumour, and assessment of vascularity may be a useful prognostic indicator for MPM patients. © 1999 Cancer Research Campaign